Implementasi Maze Mapping pada Robot Line Follower untuk menentukan Shortest Path - Yurliansyah Hirma Fajar; Dahnial Syauqy; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In tracing a maze, in addition to finding a way out or a finish point, the robot will be more efficient if it can find the shortest route of the maze. The Line Follower Robot used to complete this line-shaped maze uses a TCRT5000 sensor consisting of 5 infrared sensors as an eye to detect the black line path of the maze. In tracing the maze, the robot uses the right hand rule rules. The mapping process using Maze Mapping method to save code of the array, then the robot will simplify the code that has been used, by using the shortest path algorithm, so that when the robot start again, robots will run according to the simplified path. The final result of the study is the comparison of time and the length distance from start to finish Ì§ robots that use maze mapping, compare robots that do not use it. The test results of detecting black lines performed by the TCRT5000 sensors with 10 times experiments, each infrared sensor has a 0% error rate. The test results in mapping with 57 times experiments, generating robots moving according to the condition of the line and input from the infrared sensor, then the storage of the data array also corresponds to the movement of the robot. The average time and distance is taken from start to finish, for robot that do not use maze mapping and shortest path is 28.1 seconds and 364 cm, with 6 test times. While the average time and distance traveled start to finish for robots that use maze mapping and shortest path is 17.27 seconds and 284.5 cm with 6 test times. Then the robot that uses maze mapping and shortest path is faster 10.83 seconds and shorten the distance of 79.5 cm.